Prevalence of the Acute Respiratory Infections and Associated Factors in the Rural Areas and Urban Slum Areas of Western Maharashtra, India: A Community-Based Cross-Sectional Study - Murarkar, Sujata; Gothankar, Jayashree; Doke, Prakash; Dhumale, Girish; Pore, Prasad D.; Lalwani, Sanjay; Quraishi, Sanjay; Patil, Reshma S.; Waghachavare, Vivek; Dhobale, Randhir; Rasote, Kirti; Palkar, Sonali; et al. (Frontiers in Public Health, 2021)
Acute respiratory infections (ARIs) continue to be the most important cause of morbidity and mortality among under-five children. Some demographic and environmental factors are associated with ARIs among under-five children. The present study was conducted with the objectives to estimate the prevalence of ARIs among under-five children in rural areas and densely populated urban slums in Maharashtra, India, and to assess the association of the selected sociodemographic and household environmental factors with ARI. The study was conducted in 16 selected clusters from rural areas and densely populated urban areas of two districts in Maharashtra, India. Structured and validated proforma was used for collecting data on sociodemographic and household environmental risk factors. A total of 3,671 under-five children were surveyed. The prevalence of ARIs for the preceding month was 50.4%. It was higher among children living in rural areas (54.2%) than children living in urban areas (46.7%) (p =0.01). The prevalence of ARIs was reported to be 51.4% and 49.4% in boys and girls respectively. In Multivariate analysis, the researchers found that living in a rural area (p= 0.01) and parental smoking (p=0.04) were significantly associated with the ARIs. An intervention like reducing parental smoking habits at the household level may reduce ARIs.